Ada apa dengan financial distress? - Karmila; Nursapriana (Academic Bright Collaboration, 2023)
The purpose of this study is to analyze what is behind the occurrence of financial distress in companies and the factors that affect them. This study uses the metasynthesis method by analyzing the results of previous qualitative research related to the topic of financial distress. Based on a meta-synthesis of 12 research articles, several potential causes of financial distress in companies were identified, including: (1) poor corporate governance; (2) managerial implications such as poor capital management, liquidity and profitability; (3) an unbalanced proportion of the board of commissioners; (4) low operating capacity; (5) high levels of liquidity; (6) incompetence manage debt; and (7) certain types of companies that are vulnerable to financial problems. In addition, the financial distress prediction model can be used as an early warning of such conditions for company management. In conclusion, the company's management must regularly and carefully monitor the financial condition of the company, maintain liquidity and profitability, and apply good corporate governance in order to avoid the risk of financial distress that can lead to bankruptcy.